Facile and environmentally-friendly fabrication of robust composite film with superhydrophobicity and radiative cooling property. (10th November 2022) - Nie, Shijin; Tan, Xinyu; Li, Xinyi; Wei, Ke; Xiao, Ting; Jiang, Lihua; Geng, Jialing; Liu, Yuan; Hu, Weiwei; Chen, Xiaobo
Abstract: Endowing products used outdoors with superhydrophobicity and radiative cooling (RC) properties can decrease pollution caused by dust and heat accumulation resulting from the absorption of solar light, which is significant for prolonging life and maintaining the performance of these products. However, it is still challenging to find a facile and environmentally-friendly method to simultaneously achieve such two properties on the same film. Herein, we developed a composite film consisting of γ-methacryloxypropyl trimethoxy silane (KH-570), polydimethylsiloxane (PDMS), and SiO2 particles by a layered coating method, which exhibits strong sunlight reflectivity (>85%), high thermal-infrared emissivity (>0.95) and robust superhydrophobicity (162°). The as-obtained film achieves a sub-ambient temperature drop of 15 °C under direct sunlight. The preparation of the composite film can avoid using the reagents containing fluorine, which is environmentally friendly. The film can firmly adhere to different substrates such as glass and aluminum, which can widen the application scopes of this film. Furthermore, the composite film exhibits good durability during the wetting, outdoor daytime radiative cooling and mechanical abrasion tests, which is beneficial to the practical outdoor application of this film. Graphical abstract: Image 1 Highlights: The K/P composite film with superhydrophobicity and radiative cooling property. The K/P composite film exhibits superhydrophobicity with WCA of 162° and SA of 2°. The maximum ΔT is about 15 °C due to the high reflectivity(>85%) and emissivity(>0.95). After 200 abrasions, the WCA maintains at about 155°, and the highest ΔT reaches 11 °C.